Oligoclonal IgG Antibody Response in the Central Nervous System to Different Measles Virus Antigens in Subacute Sclerosing Panencephalitis - Vandvik, Bodvar (1973)
Agarose electrophoresis of cerebrospinal fluid from two patients with subacute sclerosing panencephalitis revealed in both cases several homogeneous bands in the intermediate and basic gammaglobulin region. The bands were identified as IgG with various degrees of kappa or lambda light-chain restriction in crossed immunoelectrophoresis. Homogeneous IgG bands were separated by preparative agarose electrophoresis and were found to represent measles virus-specific antibodies. Antibody activities against different virus products (hemolysin, hemagglutinin, and nucleocapsids) were carried by different populations of IgG. In both cerebrospinal fluid materials, antibodies to the virus hemolysin and to virus nucleocapsids were found to be relatively more basic than the antibodies to virus hemagglutinin, which appeared in the basic intermediate gammaglobulin region. We conclude that the oligoclonal IgG bands in cerebrospinal fluid of patients with subacute sclerosing panencephalitis represent homogeneous measles virus antibodies. In some instances, the IgG bands appeared to fulfill criteria of monoclonality on the basis of their electrophoretic homogeneity, selective light-chain type, and specific antibody activity.